Secularism: meaning, kinds and characteristics - Ashimi, Tijani Ahmad (International Journal of Scientific and Research Publications, 2021)
Abstract: Secularism is an ideology that advocates complete division and separation of this world and the world to come. It is defined as an elimination of man from religion and then from metaphysical control over his reason and his language. It invites people to separate between religion and politics, it also calls people to separate faith from routine activities or complete elimination of metaphysical realities from daily affairs, on the ground that metaphysical world or religious affairs can create obstacles and barriers to human development and progress. As such, the physical world and its fascination should be the first priority and main target of rational being. Based on this fact, this paper by applying analytical and comparative methods aims to explore the true etymology of secularism and investigates its various definitions. Next, the paper will further explore the kinds and characteristics of secularism as an ideology that attempts to separate religion from daily activities. Lastly, the article will also compare this ideology to Islamic worldview, i.e we will investigate whether secularism is compatible with the right teaching of Islam and that will be followed by comprehensive concluding remarks. Keywords: Secularism, Islam, naturalism. Religion, Qur’an , Christianity